2021
DOI: 10.31729/jnma.6809
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Abnormalities in Newly Diagnosed Primary Hypothyroidism in a Tertiary Care Centre of Western Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Thyroid hormones have a major influence on synthesis, mobilization and metabolism of lipids. Hypothyroidism accounts for a notable cause of secondary dyslipidemia. This can increase the risk for cardiovascular morbidity and mortality. This study was performed to find out the prevalence of lipid profile abnormalities in newly diagnosed primary hypothyroid states. Methods: This descriptive cross-sectional study was conducted among 71 patients in the context of newly diagnosed primary hypothyroidism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The following studies provide some examples of the changes in lipid parameters seen with overt hypothyroidism [ 28 , 29 , 31 33 ]. In one study of 58 individuals presenting with overt hypothyroidism and a mean TSH of 42 mIU/L, 34.5% had high TC levels, 56.9% had high LDL-C levels, 69% had high TG levels, and 62.1% had low HDL-C levels [ 33 ]. Another study examined 268 patients presenting with primary hypothyroidism (mean TSH not provided) who were not receiving lipid-lowering therapy.…”
Section: Lipid Changes With Overt Hypothyroidismmentioning
confidence: 99%
“…The following studies provide some examples of the changes in lipid parameters seen with overt hypothyroidism [ 28 , 29 , 31 33 ]. In one study of 58 individuals presenting with overt hypothyroidism and a mean TSH of 42 mIU/L, 34.5% had high TC levels, 56.9% had high LDL-C levels, 69% had high TG levels, and 62.1% had low HDL-C levels [ 33 ]. Another study examined 268 patients presenting with primary hypothyroidism (mean TSH not provided) who were not receiving lipid-lowering therapy.…”
Section: Lipid Changes With Overt Hypothyroidismmentioning
confidence: 99%
“…Leonidas H et al also showed that elevated TSH levels were associated with elevated LDL-C, LDL/HDL-C, and TC levels, and that TSH abnormalities were a risk factor for abnormal lipid metabolism [40]. Moreover, supplementation with thyroid hormone reversed the increase in lipid levels [41][42][43]. In this study, it was found that there was no signi cant difference in thyroid function in different iodine nutrition levels, and after adjusting for thyroid function, iodine nutrition was still observed to in uence blood lipids.…”
Section: Discussionmentioning
confidence: 99%
“…ApoAV is crucial to the control of TG. Levels of TGs may potentially be explained by decreased ApoAV activity in hypothyroidism [63].…”
Section: Tag/hdlmentioning
confidence: 99%